P-B9 TSCQ study: A randomized, open-label controlled trial of daily trimethoprim-sulfamethoxazole or weekly chloroquine among adults on antiretroviral therapy in Malawi. (January 2016) - Laurens, Matthew; Mungwira, Randy; Nyirenda, Osward; Divala, Titus; Kanjala, Maxwell; Muwalo, Francis; Mkandawire, Felix; Nyangulu, Wongani; Mwinjiwa, Edson; Taylor, Terrie; Mallewa, Jane; Plowe, Christopher; et al.
Abstract : Before antiretroviral therapy (ART) became widely available in sub- Saharan Africa, several studies demonstrated that daily trimethoprim- sulfamethoxazole (TS) prophylaxis reduced morbidity and mortality among HIV-infected adults by preventing malaria, respiratory infections and diarrhea. However, the applicability of results to individuals already on ART in sub-Saharan Africa and the relative benefits of malaria prevention compared to antibacterial prophylaxis in terms of long-term outcomes have not been definitively evaluated. In 2012, a randomized controlled, open label, phase III trial of continuing TS prophylaxis compared to discontinuing TS prophylaxis and starting weekly chloroquine (CQ) prophylaxis or simply discontinuing TS prophylaxis was initiated. This study aims to determine if TS continues to benefit HIV-infected Malawian adults after good response to ART. Comparing the use of TS, which prevents both malaria and bacterial infection to CQ, which prevents only malaria, will distinguish the relative impact of each regimen vis-à-vis health outcomes and virological control among adults on ART. The study will recruit a total 1400 HIV-infected adults with nondetectable viral load and CD4 count >250/mm 3 from 2 antiretroviral therapy clinics in Malawi and will follow them until 2018. To date, the cohort has been extremely healthy with a cumulative rate of 6.0 WHO clinical stage 3 and 4 events and deaths per 100 person-years of follow up. The study will have >80% power to detect a 35% reduction in these primary endpoint events in the TS or CQ arms compared to those receiving no prophylaxis. The results of this study will inform HIV management in all malaria-endemic countries.